Coaching Beginning Teachers - Veenman, Simon; de Laat, Hanneke; Staring, Corine ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This study describes the effects of a program designed to train Dutch primary school teachers in skills needed to coach and act as mentors for beginning teachers. The study investigated whether mentors who participated in the training program would implement the target coaching skills and whether the beginning teachers coached by the mentors would perceive a change in mentors' coaching skills. An experimental group included 15 trained mentors and their beginning teachers. A control group included seven untrained mentors and their beginning teachers. The training involved a comprehensive manual and a 2-day workshop. Participants received the manual to study before the workshop. Prior to the training, each mentor conducted an audiotaped coaching conference with a beginning teacher. After the training, trained and untrained mentors again conducted audiotaped coaching conferences with the same beginning teachers. Coaching skills of trained and untrained mentors were rated by expert judges and by the beginning teachers. Beginning teachers also estimated the effects of the coaching on their own practice. Analysis of the judges' observations indicated there was a significant treatment effect for the coaching skills related to the development of autonomy, feedback, and encouragement of self-reflection. Pre- and post-training ratings from the beginning teachers showed no significant treatment effects, as the beginning teachers rated their mentors' coaching skills very favorably at pretest. (Contains 27 references.) (SM)
ERIC Note: Paper presented at the European Conference on Educational Research (Ljubljana, Slovenia, September 17-20, 1998).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Beginning Teacher Induction; Beginning Teachers; Elementary Education; Elementary School Teachers; Faculty Development; Feedback; Foreign Countries; Mentors; Teacher Attitudes; Teacher Improvement; Netherlands; Reports, Research; Speeches/Meeting Papers